Design and fabrication of Stewart platform for tracking and vibration isolation for free space optic transmission - Antong, Hasmawati; Abdul Muthalif, Asan Gani (s.n, 2012)
Recently, many researchers are interested with Free Space Optics (FSO) communication since its deliver wireless data transmission between transceivers. One of the key challenges with FSO systems is maintaining alignment between transceivers. Since the beam signal is transmitted through the free space, the optical signal propagation is affected by atmospheric turbulence and pointing error. Hence, tracking system is required to reduce or eliminate the misalignment between the transmitter and receivers. In order to implement this system, a prototype model perform experiments is required. This research project and grant aims to develop/fabricate the required prototype model to study the implementation of tracking system